2016
DOI: 10.1002/jmri.25203
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐weighted quantitative MRI to diagnose benign conditions from malignancies of the anterior mediastinum: Improvement of diagnostic accuracy by comparing perfusion‐free to perfusion‐sensitive measurements of the apparent diffusion coefficient

Abstract: The use of perfusion-free ADC measurements significantly improves diagnostic accuracy of DW-MRI in differentiating benign conditions from malignancies of the anterior mediastinum. J. Magn. Reson. Imaging 2016;44:758-769.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 36 publications
1
29
0
1
Order By: Relevance
“…Similar results were reported by Ohno et al, who found better performance of ADC compared to maximum standardized uptake value obtained from PET‐CT as a quantitative predictor of tumor treatment response after chemoradiotherapy in nonsmall‐cell lung cancer . However, the aim of our study was to assess the repeatability of different protocols of ADC measurement that are generally used in other organs and compartments . Thus, the best method of ADC measurement for clinical application in DW‐MRI of the pleura and its benefit in evaluating and predicting treatment response are yet to be determined by means of further studies.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Similar results were reported by Ohno et al, who found better performance of ADC compared to maximum standardized uptake value obtained from PET‐CT as a quantitative predictor of tumor treatment response after chemoradiotherapy in nonsmall‐cell lung cancer . However, the aim of our study was to assess the repeatability of different protocols of ADC measurement that are generally used in other organs and compartments . Thus, the best method of ADC measurement for clinical application in DW‐MRI of the pleura and its benefit in evaluating and predicting treatment response are yet to be determined by means of further studies.…”
Section: Discussionsupporting
confidence: 71%
“…Further studies are required to validate our results in larger cohorts with more homogeneous groups of pleural abnormalities. Third, ADC values are also influenced by a number of parameters other than the manual method of ROI positioning . However, all parameters were set as recommended in consensus articles on DW‐MRI and kept constant for all cases in order to compare ADC values between different measurement protocols .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI offers the ability to assess additional tissue‐specific parameters through the use of DWI and DCE. In the thorax, these techniques have shown potential in the evaluation of a variety of conditions, including lung cancers, pulmonary nodules, anterior mediastinal masses, and pleural disease . While their penetrance into current routine clinical practice has lagged behind expectations, familiarity with these techniques is important when considering protocol design, as they allow for noninvasive tissue characterization that is not available with chest radiography, CT, and FDG‐PET/CT.…”
Section: Building Blocksmentioning
confidence: 99%
“…In general, most groups obtain at least one low b‐value (0–100 sec/mm 2 ) and one high b‐value (600–800 sec/mm 2 ). Many groups also include an additional b‐value between 50 or 100 and 800 sec/mm 2 , such as 400 sec/mm 2 , which can improve quantitative ADC calculation and provide another b‐value in a series of image sets with progressively increasing b‐values . Readers can use these series to identify areas of increased signal on higher b‐value sequences, which often correspond to sites of pathology.…”
Section: Building Blocksmentioning
confidence: 99%